Asia Pacific roadmap for innovative technologies in the forest sector - Roshetko, J.M.; Pingault, N.; Quang Tan, N.; Meybeck, A.; Matta, R.; Gitz, V. (FAO and FTA, 2022)
As highlighted by FAO’s Third Asia-Pacific Forest Sector Outlook Study (APFSOS III), the use of innovative technologies – from digital technologies, biological technologies, processing technologies and new wood-based products, to social innovations and innovative finance mechanisms – have the potential to revolutionize forest management and to make critical contributions to sustainable development along forest value chains.